2017
DOI: 10.1016/j.jpurol.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Blind ending vessels on diagnostic laparoscopy for nonpalpable testis: Is a nubbin present?

Abstract: In this large multi-institutional series, blind ending vessels were associated with a nubbin noted during inguinal or scrotal exploration in the majority of cases. Based on this series if the surgeon's goal is to remove all nubbins, exploration is necessary regardless of vessel appearance. However, viable testicular elements were rarely identified and only when either a non-atretic vas or any vessels were observed to enter the ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
3
5
0
1
Order By: Relevance
“…In all our patients, laparoscopic abdominal exploration was performed first when the testis was not palpable under anesthesia. Intra-abdominal testis frequency in NPT patients has been defined as 40-61% in some studies [9,12,14,15]. In our study, 25 (46.2%) of the 54 NPTs were found to have testis in the abdomen.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In all our patients, laparoscopic abdominal exploration was performed first when the testis was not palpable under anesthesia. Intra-abdominal testis frequency in NPT patients has been defined as 40-61% in some studies [9,12,14,15]. In our study, 25 (46.2%) of the 54 NPTs were found to have testis in the abdomen.…”
Section: Discussionsupporting
confidence: 50%
“…An important evaluation step in patients without testis in intra-abdominal exploration is the evaluation of the testicular artery. The AUA and EAU/ESPU guidelines recommend inguinal exploration if the testicular vessels appear to have entered the inguinal canal, while further processing is not recommended in the presence of a vessel with a blind-ending [15,19]. However, Sturm et al reported that inguinal/scrotal nubbin was present in 72% of 36 cases whose testicular vessels ended blindly in laparoscopic exploration [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate over the management of boys with testicular regression syndrome is still ongoing. The exploration and excision of testicular remnants, as well as blind ending vessels associated with a nubbin, are recommended by many authors, as seminiferous tubules and germ cells may be found in them [ 31 , 32 ]. However, only single cases of germ cell neoplasia in a testicular remnant are reported in the literature [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the laparoscopy, given that the internal ring was closed, the testicular nubbin was excised through a small inguinal incision. 4 The histological exam revealed fibrous–muscular–adipose tissue.…”
Section: Case Reportmentioning
confidence: 98%